KEKUATAN LAKI-LAKI “DI BAWAH KETIAK PEREMPUAN”: MEMBANGUN PERSPEKTIF GENDER DI SUMATERA BARAT - Reza Fahmi (Universitas Islam Negeri Imam Bonjol Padang, 2013)
The Minangs are the world's largest matrilineal society; properties such as land and houses are inherited through female lineage. Some scholars argue that this might have caused the diaspora (Minangkabau,